Modern foreign languages: decision-making, motivation and 14-19 schools - Parrish, Abigail (Cambridge journal of education, 2020)
This article reports on an exploratory study comparing motivation and student choice in modern foreign language lessons in secondary schools (11-16 or 11-18) and schools for 14-19 year olds in England. The study uses data gathered from 634 Year 10 students (aged 14-15) and uses Self-Determination Theory to compare motivation amongst students in the two types of schools. It finds that student motivation differed significantly in each, with students in 14-19 schools displaying more autonomous motivation. Students in schools in this category were less likely to have been given a choice as to whether or not to take the subject than their peers, suggesting that they may feel autonomous in ways not governed by subject choice. Possible reasons for the differences in motivation in the two kinds of school are discussed and directions for future study proposed.